Travel cooperation cost allocation - Chengming Zhu; Yanyan Chen; Yugang Wang; Yao Lu; Changxi Ma (Advances in Mechanical Engineering, 2017)
Reasonable travel cooperation cost allocation is the premise of promoting travel cooperation. Travel cooperation is the premise of relieving traffic congestion. From the perspective of cooperation, the connotation and basic principle of travel cooperation cost allocation are analyzed. Also the basic condition and specific allocation method of travel cooperation cost allocation are discussed. Travel cooperation cost allocation model is established according to travel cooperation level. The reasonability of travel cooperation cost allocation method and traveler acceptance level on allocation method are analyzed through questionnaire survey. The condition of travel giving preference to public transit is analyzed. The survey result shows that travel cooperation cost allocation method is reasonable and feasible.